A Hoosier holiday - Dreiser, Theodore, 1871-1945 (Indiana University Press, 1997)
By 1914, Theodore Dreiser was a successful writer with an international reputation, as well as a fixture on the New York literary scene. He had not been back to Indiana, his home state, in over twenty years when he was approached by his friend Franklin Booth, a respected and very successful artist, to make the trip together by automobile. The result is a narrative brimming with detail and the first modern work of American road literature, capturing the euphoric freedom to be found behind the wheel of a car.